2003
DOI: 10.1007/s00265-003-0694-0
|View full text |Cite
|
Sign up to set email alerts
|

Earlier sex change in infected individuals of the protogynous reef fish Thalassoma bifasciatum

Abstract: Sex allocation theory for sequential hermaphrodites predicts the size at which an individual should change sex, given the different relationships between individual size and reproductive success in the two sexes. We studied a host-parasite system where the myxozoan Kudoa ovivora infects the ovaries of the reef fish Thalassoma bifasciatum, a protogynous sequential hermaphrodite. The parasite sporulates in the host's eggs and renders them infertile. It is thus expected to reduce the female's reproductive success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Moreover, in the sequential hermaphrodite, the fish Thalassoma bifasciatum (Bloch), K. ovivora influences sex allocation of its host. Thus, it was suggested that females infected by this parasite not only have a lower reproductive success, but also change sex earlier and at a smaller size than uninfected ones (Schärer and Vizoso 2003). Such situation could also lead to a quick loss of the parasite as the ovarian tissue will be replaced by testes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the sequential hermaphrodite, the fish Thalassoma bifasciatum (Bloch), K. ovivora influences sex allocation of its host. Thus, it was suggested that females infected by this parasite not only have a lower reproductive success, but also change sex earlier and at a smaller size than uninfected ones (Schärer and Vizoso 2003). Such situation could also lead to a quick loss of the parasite as the ovarian tissue will be replaced by testes.…”
Section: Discussionmentioning
confidence: 99%
“…Females of Thalassoma bifasciatum with Kudoa ovivora infections in the ovary change sex earlier and at a smaller size, thus gaining a reproductive advantage. Such sex change represents 'host death' from the parasite's point of view, as the host tissue required for sporogony disappears (Schärer and Vizoso 2003).…”
Section: Sex-specific Infectionmentioning
confidence: 99%
“…Animals and plants live in complex environments in which they interact with many organisms both antagonistically and mutualistically, and this is an underexplored factor of sex change especially in animals (e.g. Schärer & Vizoso, ). In plants, it has been suggested that antagonistic and mutualistic interactions play an important role in the evolution and maintenance of unisexuality (Vega‐Frutis et al ., ), but sex change has received little attention in this context (Audran & Batcho, ).…”
Section: Future Directionsmentioning
confidence: 99%